Melting of ³He in a phase-separated solid ³He - ⁴He mixture - Haley, R.P.; Adams, E.D. (Физика низких температур, 1997)
The melting pressure of the ³He-rich phase, which is formed after phase separation of a mixture of 0.6% ³He in ⁴He, has been studied in the temperature range 1–150 mK, below the phase-separation temperature Tps, at pressures between 2.78 and 3.56 MPa. Measurements were made with the mixture confined in a silver sinter, and also in an open volume for comparison. An elevation of the melting pressure relative to pure ³He of up to 60 kPa in the sinter cell and 20 kPa in the open-volume cell was observed. Hysteresis between the freezing and melting temperatures was found for both cells, similar to that observed for pure ³He in small pores. The results of Schrenk et al. for heat capacity measurements on a similar system are discussed.